Pengaruh Sektor Pariwisata terhadap Produk Domestik Regional Bruto pada Kabupaten dengan Kunjungan Wisata Tertinggi di Kabupaten Bulukumba - Sitti Hasbiah (Institut Nalanda, 2026)
This study aims to analyze the potential and development of tourist destinations in Bulukumba Regency, one of the regions with leading tourist attractions in South Sulawesi Province. Bulukumba Regency is known for its diverse tourism potential, ranging from marine tourism, natural tourism, cultural tourism, to historical tourism, which can be a source of driving regional economic growth. Tourist destinations such as Tanjung Bira Beach, the Pinisi shipbuilding area, and various local cultural attractions demonstrate Bulukumba's comparative advantage in the tourism sector. This study focuses on identifying tourist attractions, the availability of supporting facilities, accessibility, promotion, and the role of the community in developing tourist destinations. Tourism development in Bulukumba Regency is not only directed at increasing the number of tourist visits, but also to strengthen the local economy, open business opportunities, create jobs, and maintain cultural and environmental sustainability. Therefore, tourism destination management needs to be carried out in a planned, sustainable manner, and based on local potential. The results of the study indicate that Bulukumba Regency's tourist destinations have significant potential to be developed as leading tourist destinations. However, such development still requires support in terms of infrastructure, service quality, digital promotion, cleanliness of tourist areas, and active involvement of the community and local government. With proper management, the tourism sector in Bulukumba Regency can become an important pillar in driving regional economic development and improving community welfare.